As interjeições e locuções interjetivas nas tiras em quadrinhos sob a abordagem discursiva. - Tomazetto, Simone Aparecida (2012)
This paper aims to present considerations that may contribute to the shape linguistic and semantic function as discursive situation of interjections and phrases interjetivas, from the theoretical assumptions with main focus on studies Gonçalves (2002), Bakhtin (2000, 2002a, 2002b), Bakhtin / Voloshinov (2004) and Marcuschi (2007). The intention of this paper is to reflect and discuss the considerations of the use of interjections and phrases interjetivas acts as expressive, natural conversation, expressing your feelings through words and body language, featuring different senses of semantic and discursive. For data analysis, this research sought supports the theories of speech acts, based on theoretical and Austin (1962) and Searle (1981), in conversation analysis with theoretical support in Marcuschi (1991) and Dionysus (2011), and in the language of visual imagery, verbal and non-verbal of comic strips with methodological studies of Gumperz (1998) and Ramos (2010). The corpus chosen for this research consists in comic strips, selected the Folha de São Paulo in 1970 and 1990, in textbooks and electronic sites. This is a survey of the basic nature of the qualitative type that you want to analyze the form and function of interjections and phrases within interjetivas comic strips, observing the discursive and semantic factors. The analysis results show that, as of interjections and phrases can be interjetivas list the basic emotions of expressive acts and explain its flexibility from factors of pragmatic, and expressive acts that are not in the service of transmitting a information, but the service of a manifestation of an emotional state, observed in speech acts and conversation between characters when it materializes the image visual communication, verbal and nonverbal. Thus, it is expected that this research will bring a contribution for teachers of English, which can be used as a source of research, contributing to the construction of knowledge of teachers and students in the context of the classroom as a way of meaningful learning.